The Gengnianchun recipe attenuates insulin resistance-induced diminished ovarian reserve through inhibiting the senescence of granulosa cells - Gao, Hongna; Gao, Lingyun; Rao, Yanqiu; Qian, Laidi; Li, Mingqing; Wang, Wenjun (Frontiers in Endocrinology, 2023)
Insulin resistance (IR) is known to be associated with patients with polycystic ovary syndrome (PCOS), but the effects and mechanisms of IR on diminished ovarian reserve (DOR) remain unclear. In this study, we aim to investigate the effects of IR on ovarian reserve in mice, to explore the effects of high concentrations of insulin on the function of ovarian cells in vitro, and to validate the hypothesis that Gengnianchun recipe (GNC) helps to attenuate the DOR caused by IR through reducing senescence of granulosa cells. Estrus cycle, follicle count, and sex hormone levels were detected to evaluate the ovarian function in IR mouse model established by feeding high-fat diet (HFD). KGN cells (human granulosa cell line) were treated with high concentrations of insulin, and the staining for Senescence-Associated β-galactosidase (SA-β-gal), cell cycle, and mRNA and protein of genes related to cell aging were detected. Mice treated with HFD were fed with metformin, GNC or saline solution for six weeks by oral gavage. HOMA-IR, OGTT, FBG and FINS were examined to confirm the status of IR. Then estrus cycle, follicle count, and sex hormone levels were detected to evaluate the ovarian function. The mRNA and protein of genes related to cell aging were detected in ovarian tissue of mice in each group. The results demonstrated that IR reduced ovarian reserve of mice, and high dose insulin made granulosa cells senescent. There has been a considerable improvement in HFD-induced IR status after the treatment of metformin or GNC. Not only that, the expression levels of aging-associated biomarkers were much lower in mice of GNC group than that in mice of metformin group, which were significantly decreased in mice of metformin group or GNC group compared to HFD group. At the same time, higher counts of different stages and shorter diestrous in metformin or GNC group compared to HFD group indicate that ovarian aging has been largely reversed. This work showed that IR impaired ovarian reserve, high concentrations of insulin can induce granulosa cells aging, and GNC attenuated ovarian function through inhibiting IR-induced cell aging.